Polymerization of lactic acid oligomers under microwave irradiation - Guba, G.Ya.; Gusar, A.O.; Mamaeva, E.A.; Popova, V.А.; Dolgov, I.R.; Bakibayev, A.A.; Ahmedjanov, R.R. (KSU publ., 2019)
The kinetics of the polymerization of lactic acid oligomers (LAO) was studied for the first time at various microwave irradiation powers (MW) in the presence of Sn(Oct)2/benzyl alcohol (C6H5CH2OH) catalyst and toluenesulfonic acid (TSA). LAO was polymerized in a multimodal reactor in a vacuum while sparging with nitrogen at powers of 130, 280, 360 W. The optimal concentrations of catalysts and initiator were determined, which represent 0.03 % Sn(Oct)2/C6H5CH2OH and 0.3–0.4 % TSA by weight of LAO. It was established that the polymerization of LAO in the presence of TSA proceeds already at 130 W. As the MW power increases, the rate of LAO polymerization increases. When Sn(Oct)2/C6H5CH2OH was used as a catalyst, the LAO polymerization process proceeds at a noticeable rate at 280 W, and after 25 min the molecular weight was about 20,000 Da. During the polymerization of LAO in the presence of catalysts at 360 W, lactide forms along with the formation of polylactic acid (PLA). Using the methods of IR and NMR spectroscopy, the structure of the obtained substances was studied. The synthesized PLA samples are optically pure; the optical rotation angle is 156–158 degrees×ml/dm×g. It has been suggested that during LAO polymerization under MW conditions, the so-called «non-thermal microwave effect» is observed, that is, at the same temperature (215 °C), but at different powers (280 W and 360 W), the LAO polymerization proceeds at different rates.
Keywords: microwave irradiation; lactic acid; polylactic acid; lactic acid oligomers; NMR spectroscopy; IR spectroscopy; specific optical rotation; catalyst